An investigation into the depth and time dependent behavior of UV cured 3D ink jet printed objects - Chen, Xuesheng; Ashcroft, Ian; Tuck, Christopher; He, Y.F.; Hague, Richard J.M.; Wildman, Ricky D. (Cambridge University Press, 2017)
An ultra-violet (UV) curable ink jet 3D printed material was characterized by an inverse finite element modeling (IFEM) technique employing a nonlinear viscoelastic–viscoplastic (NVEVP) material constitutive model; this methodology was compared directly with nanoindentation tests. The printed UV cured ink jet material properties were found to be z-depth dependent owing to the sequential layer-by-layer deposition approach. With further post-UV curing, the z-depth dependence was weakened but properties at all depths were influenced by the duration of UV exposure, indicating that none of the materials within the samples had reached full cure during the 3D printing process. Effects due to the proximity of an indentation to the 3D printed material material-sample fixing interface, and the different mounting material, in a test sample were examined by direct 3D finite element simulation and shown to be insignificant for experiments performed at a distance greater than 20 lm from the interface.